Cure monitoring of a UV cured epoxy resin using a long period grating Mach- Zehnder interferometer - Buggy, Stephen J.; Murphy, Richard P.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2007)
A cascaded long period grating Mach-Zehnder interferometer is used to monitor the change in refractive index of a UV cured epoxy resin over a cure cycle. Fourier techniques are used to calculate the phase shift and frequency spectral amplitude of the associated fringe pattern during the cure. The results are compared with the refractive index change during cure calculated using a Fresnel reflection based technique.
Keywords: Cure sensor; Fresnel refractometer; Long period grating; Optical fibre